Oxygen uptake in Pacific salmon Oncorhynchus spp.: when ecology and physiology meet. Issue 1 (18th November 2015) - Eliason, E. J.; Farrell, A. P.
Abstract : Over the past several decades, a substantial amount of research has examined how cardiorespiratory physiology supports the diverse activities performed throughout the life cycle of Pacific salmon, genus Oncorhynchus . Pioneering experiments emphasized the importance of aerobic scope in setting the functional thermal tolerance for activity in fishes. Variation in routine metabolism can have important performance and fitness consequences as it is related to dominance, aggression, boldness, territoriality, growth rate, postprandial oxygen consumption, life history, season, time of day, availability of shelter and social interactions. Wild fishes must perform many activities simultaneously ( e.g . swim, obtain prey, avoid predators, compete, digest and reproduce) and oxygen delivery is allocated among competing organ systems according to the capacity of the heart to deliver blood. For example, salmonids that are simultaneously swimming and digesting trade‐off maximum swimming performance in order to support the oxygen demands of digestion. As adult Pacific salmonids cease feeding in the ocean prior to their home migration, endogenous energy reserves and cardiac capacity are primarily partitioned among the demands for swimming upriver, sexual maturation and spawning behaviours. Furthermore, the upriver spawning migration is under strong selection pressure, given that Pacific salmonids are semelparous (single opportunity to spawn). Consequently, these fishes optimize energy expenditures in a number of ways: strong homing, precise migration timing, choosing forward‐assist current paths and exploiting the boundary layer to avoid the strong currents in the middle of the river, using energetically efficient swimming speeds, and recovering rapidly from anaerobic swimming. Upon arrival at the spawning ground, remaining energy can be strategically allocated to the various spawning behaviours. Strong fidelity to natal streams has resulted in reproductively isolated populations that appear to be locally adapted physiologically to their specific environmental conditions. Populations with more challenging migrations have enhanced cardiorespiratory performance. Pacific salmonids are able to maintain aerobic scope across the broad range of temperatures encountered historically during their migration; however, climate change‐induced river warming has created lethal conditions for many populations, raising conservation concerns. Despite considerable research examining cardiorespiratory physiology in Pacific salmonids over the last 70 years, critical knowledge gaps are identified.